2005
DOI: 10.1002/jbm.b.30341
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical evaluation of bone samples following alendronate therapy in healthy male dogs

Abstract: Alendronate and other bisphosphonates are clinically efficacious in treating postmenopausal osteoporosis, Paget's disease and hypercalcemia associated with malignancy. Because bisphosphonates are being considered for use in younger patients with joint replacements to prevent osteolysis, and for stress fracture prophylaxis in military recruits, it is important to know how bisphosphonate therapy affects healthy bone. We sought to determine whether bones from healthy male dogs exhibit alterations in structural or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Our previous investigations of femora in a canine total hip arthroplasty model demonstrated that a prolonged bisphosphonate treatment over 23 weeks did not alter whole bone mechanical properties, such as fracture toughness, elastic modulus, or tensile strength [33]. In a separate evaluation, the torsional properties of bisphosphonate-treated bones were also unchanged, as were the trabecular modulus, strength and density [9]. Histomorphometric data similarly demonstrate no adverse effects on bone structure or mineralization [48].…”
Section: Article In Pressmentioning
confidence: 73%
See 2 more Smart Citations
“…Our previous investigations of femora in a canine total hip arthroplasty model demonstrated that a prolonged bisphosphonate treatment over 23 weeks did not alter whole bone mechanical properties, such as fracture toughness, elastic modulus, or tensile strength [33]. In a separate evaluation, the torsional properties of bisphosphonate-treated bones were also unchanged, as were the trabecular modulus, strength and density [9]. Histomorphometric data similarly demonstrate no adverse effects on bone structure or mineralization [48].…”
Section: Article In Pressmentioning
confidence: 73%
“…Clinically, thicker peri-implant cortical bone improves the torsional strength of the bone as suggested by significantly increased polar moment of inertia. Our previous studies have demonstrated that bisphosphonate treatment over 23 weeks does not compromise the structural or mechanical properties of the bone [9,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is based on a study which found that, in ovariectomized baboons, 2 years of alendronate treatment did not alter the mechanical properties of cortical tissue or the nonlinear strength-density correlation for trabecular bone [41]. In addition, a study on healthy male dogs showed that 23 weeks of alendronate treatment did not alter mechanical properties of trabecular bone [42]. Other limitations were that this study was a nonrandomized drug study, and only eight subjects were included in the untreated group.…”
Section: Discussionmentioning
confidence: 99%
“…Currently available bisphosphonates, notably alendronate, risedronate, and zoledronate, have been extensively tested in animal models [8,[17][18][19][20][21][22][23][24][25]. In ovariectomized rats and nonhuman primates, these agents were shown to prevent bone turnover, while increasing BMD [8,[17][18][19][20][21].…”
Section: Preclinical Datamentioning
confidence: 99%